2015
DOI: 10.1111/petr.12441
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous pentamidine for Pneumocystis carinii/jiroveci pneumonia prophylaxis in pediatric transplant patients

Abstract: SMX/TMP is the current gold standard for prophylaxis against PCP in immunocompromised pediatric patients. Currently, there are several second-line options for prophylaxis but many, including intravenous (IV) pentamidine, have not been reported to be as effective or as safe as SMX/TMP in the pediatric transplant population. This study is to determine the efficacy and safety of IV pentamidine in preventing PCP in pediatric transplant patients. A retrospective chart review was conducted to evaluate all transplant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
5
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 26 publications
3
5
0
Order By: Relevance
“…Two other studies reported no incidents of breakthrough PCP among pediatric oncology patients receiving aerosolized pentamidine for PCP prophylaxis (6, 7). The reported incidence of breakthrough PCP among pediatric oncology and solid organ transplant patients ranges from 0% to 1.3% overall (10,14,15,(17)(18)(19)(20). Our findings are comparable to breakthrough PCP incidence rates reported for TMP-SMX (5).…”
Section: Discussionsupporting
confidence: 81%
See 3 more Smart Citations
“…Two other studies reported no incidents of breakthrough PCP among pediatric oncology patients receiving aerosolized pentamidine for PCP prophylaxis (6, 7). The reported incidence of breakthrough PCP among pediatric oncology and solid organ transplant patients ranges from 0% to 1.3% overall (10,14,15,(17)(18)(19)(20). Our findings are comparable to breakthrough PCP incidence rates reported for TMP-SMX (5).…”
Section: Discussionsupporting
confidence: 81%
“…However, two of their reported cases had undergone HSCT, possibly contributing to the respiratory compromise. No patients in this study had pentamidine discontinued due to tachycardia, but pancreatitis was the reason for discontinuation in three patients (0.4%), which is similar to the rate reported by Clark et al (0.6%) (14). The rate of pancreatitis is notable; however, a sensitive definition was utilized to ensure we captured all potential cases of pancreatitis.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…It is also used to treat American cutaneous leishmaniasis and as a prophylactic for Pneumocystis jirovecii pneumonia [1]. HAT is a major public health problem in sub-Saharan Africa and is classified as one of the most neglected tropical diseases.…”
Section: Introductionmentioning
confidence: 99%